GOVERNMENT MEDIA MONITORING AND PUBLIC PERCEPTION OF TRAFFIC CONGESTION - Khoirunisa Fitriani; FX. Ari Agung Prastowo; Trie Damayanti (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study examines the implementation of media monitoring conducted by the Protocol and Leadership Communication Division (Prokopim) of the Bandung City Regional Secretariat in managing public perceptions regarding traffic congestion issues in Bandung City. The study aims to analyze the stages of media monitoring carried out by Prokopim, including planning, data collection, data visualization, data analysis, and reporting. This research employed a descriptive qualitative approach through participatory observation, structured interviews, and literature study. The findings indicate that media monitoring plays a strategic role in identifying public sentiment, mapping issue developments, and formulating evidence-based communication strategies for local government leaders. Through monitoring mass media and social media, Prokopim was able to identify public concerns, criticisms, and support related to transportation policies and traffic management in Bandung. The results of media monitoring were subsequently used to develop communication recommendations, public information strategies, and issue management approaches aimed at maintaining public trust in the government. Although the monitoring process is still conducted manually and has not fully utilized digital analytic tools, media monitoring has functioned as an important communication intelligence instrument in supporting government public relations activities.